A Dialectical Definition of Conservatism. (9th December 2015) - Alexander, James
Abstract: Conservatism is now often said to be a disposition. Against definitions of conservatism as a disposition, critics say that it is also an ideology, and against any such abstract definitions, that it is a historical entity. But no one has yet indicated how these criticisms can be used to improve the definition of conservatism. Here I argue that the dispositional understanding of conservatism, while not wrong in itself, is only the first and simplest element in what has to be an extended or dialectical definition of conservatism. This article is a statement of such a definition.